2014 IEEE Intelligent Vehicles Symposium Proceedings 2014
DOI: 10.1109/ivs.2014.6856605
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how camera configuration and environmental conditions affect appearance-based localization

Abstract: Abstract-Localization is a central problem for intelligent vehicles. Visual localization can supplement or replace GPSbased localization approaches in situations where GPS is unavailable or inaccurate. Although visual localization has been demonstrated in a variety of algorithms and systems, the problem of how to best configure such a system remains largely an open question. Design choices, such as "where should the camera be placed?" and "how should it be oriented?" can have substantial effect on the cost and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The database image sequences and evaluation image sequences were collected at different times on a single day. More extensive analyses the effects of illumination and appearance variance were presented in [4], [5], and [6]. Ideally, our experiments would use an established database, such as the KITTI benchmark [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The database image sequences and evaluation image sequences were collected at different times on a single day. More extensive analyses the effects of illumination and appearance variance were presented in [4], [5], and [6]. Ideally, our experiments would use an established database, such as the KITTI benchmark [13].…”
Section: Methodsmentioning
confidence: 99%
“…However, this is not such an onerous requirement, since such maps already exist (e.g., Google Street View). Our previous work has shown that the maps do not have to be updated very frequently, as localization is robust to changing conditions, such as seasonal variations and different weather and light conditions [5], [6].…”
Section: Related Workmentioning
confidence: 99%
“…As mentioned in [26], vision-based algorithms may have very different performance with different camera configurations and environmental conditions. This aspect of reliability and integrity is of significant importance for autonomous vehicles.…”
Section: Segmentation Reliabilitymentioning
confidence: 99%
“…SLAM has long been a classic topic in the field of robotics [14] and has become a popular research direction in autonomous driving since many drivable areas are GNSS denied, such as indoor parking lots and urban roads covered by tree branches or beside skyscrapers [15]. VSLAM, which is based on budget vision sensors, is preferred by many car manufacturers who have already equipped multiple cameras on their production cars.…”
Section: Related Workmentioning
confidence: 99%